Orang laut Johor-Riau dalam perubahan politi sehingga akhir abad ke-20 - Roziah Mohamad Ali (Tanjong Malim, 2019)
Orang laut Johor-Riau dalam perubahan politi sehingga akhir abad ke-20 by Roziah Mohamad Ali